THE CONTRIBUTION OF PLAYGROUP MANAGERS’ LEADERSHIP IN IMPROVING TUTOR PERFORMANC - Iip Saripah; Rahmawan Rahmawan (IKIP Siliwangi Bandung, 2021)
This research departs from the performance of Playgroup tutors which can be used to assess the achievement of the tutor's work in planning and implementing the learning process, as well as assessing the learning outcomes in Playgroup units. The research was conducted at the As-Salam Kp. Nagrogjaya, Pagaden District, Subang Regency. The objectives of this study were (1) to describe the leadership function of the As-Salam Playgroup manager in improving tutor performance; (2) describe the tutor's performance achievements in increasing competence. The research method was used descriptive method with a qualitative approach. The number of informants was 8 people. Based on the findings and discussion, this study obtained the results (1) the manager of the As-Salam Playgroup can actualize the functions of educators, managers, administrators, supervisors, leaders, innovators, and motivators as a form of leadership contribution in improving tutor performance; (2) the performance of the tutor is well perceived by the manager of the As-Salam Playgroup, measured by the quality of work, timeliness of work, work initiative, work ability, and communication at work.